Variation in Non-finite Constructions in English Trends Affecting Infinitives and Gerunds - Kaunisto, Mark.; Rudanko, Juhani; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book sheds new light on the nature of gerunds in English, utilizing data from very large electronic corpora in order to compare pairs of patterns viewed as constructions. It serves as a contribution to the study of complementation, an under-researched area of investigation which bridges observations at the intersection of lexico-grammar, syntax and semantics. As a result, the reader develops their understanding of the meaning and use of each pattern within the system of English predicate complementation as it has evolved in recent times. This book will be of interest to students and scholars of English linguistics, especially English grammar. Mark Kaunisto is a Senior Lecturer at Tampere University, Finland. His work includes corpus-based studies on morphological rivalry, word-formation, neologisms, and usage guidebooks. Juhani Rudanko is Professor Emeritus at Tampere University, Finland. His latest work focuses on the evolutionof predicate complementation in recent English and the application of linguistic pragmatics to the analysis of political debates in the early American Republic.
Chapter 1: Introduction -- Chapter 2: Variation between Sentential Complements: the Case of Work at -ing and Work on -ing -- Chapter 3: Semantic Roles and Complement Selection: a Case Study on the Matrix Adjective Frightened -- Chapter 4: Emergence of Covert Noun Phrase Objects: the Case of Advise against -ing -- Chapter 5: Exceptions to Bach's Generalization in Inner and Outer Core Varieties of English: the Case of Warn against -ing -- Chapter 6: New Light on -Ing Complements of Prevent, with Recent Data from Large Corpora -- Chapter 7: Conclusion. .
Keywords: Linguistics; Computational linguistics; Linguistic change; Grammar, Comparative and general -- Syntax; Linguistics -- Methodology; Theoretical Linguistics / Grammar; Computational Linguistics; Language Change; Syntax; Research Methods in Language and Linguistics